Coupling between topological edge state and defect mode-based biosensor using phononic crystal - Zaky A. Zaky; M. Al-Dossari; Ahmed S. Hendy; Yassine Bouazzi; Attia Boudjemline; Arafa H. Aly (Scientific Reports)
Abstract A wealth of details regarding an individual’s state of health, like a person’s respiratory and metabolic functioning, can be studied by analyzing the volatile molecules and atoms in human exhaled breath. Besides, the salinity of seawater is a crucial factor in understanding its characteristics because any variation in the salinity of seawater represents the variations in the hydrological, biological, and chemical distributions. In this paper, a symmetrical one-dimensional phononic structure is theoretically designed using two symmetrical crystals separated with a defective cavity. This structure has been designed to excite a topological edge state coupled with defect mode. The coupled mode achieves high sensitivity to NaCl concentration in an aqueous solution, seven times higher than the defective one. By ranging the NaCl concentration from 0 to 21%, the average sensitivity is 467 and 3160 Hz/% for defect mode and coupled modes, respectively. The bandwidth of the coupled mode of 170 Hz is much narrower than that of the defect mode of 671 Hz for detecting salinity. For detecting the increase in $$\:CO_{2}$$ concentration in dry exhaled breath by ranging the $$\:CO_{2}$$ concentration from 0 ppm to 100 ppm, the average sensitivity is $$\:32$$ Hz/ppm for coupled mode. As a result of these enhancements in the sensitivity and bandwidth of the coupled mode, the coupled mode is recommended to be used in different biosensing applications.